Sputtering of lithium and lithium compound films under deuterium and helium ion bombardment. (May 2019) - Buzi, L.; Nelson, A.O.; Yang, Y.; Kaita, R.; Krstić, P.S.; Koel, B.E.
Highlights: Pure Li films were observed to become LiD films upon D2 + irradiation before significant sputtering occurred. He + sputtering of pure Li yielded 2–3 times higher sputtering yields compared to D2 + irradiation. The Li sputtering yield upon D2 + irradiation of LiO film was lower than the LiCO sputtering yield. Upon oxidation, the temperature for complete Li desorption was increased by 350 K, while CO exposures on a pure Li layer increased its stability by 300 K. D retention saturates when irradiating Li and Li compound films with increasing incident D2 + fluences. Abstract: Conditioning of plasma facing components (PFCs) using lithium (Li) evaporation has shown to improve plasma performance in fusion devices by imposing low recycling boundary conditions. It is important to understand the retention and sputtering dynamics of deuterium (D) in Li and Li compound (LiO and LiCO) films to most efficiently make predictions on plasma performance. Energetic D2 + incident on thin Li films is shown to readily form LiD leading to a lower Li sputtering yield than the sputtering yield of pure Li. Measured sputtering yields for thin LiD films agree with previous simulations and bulk erosion measurements. The He + sputtering yield of pure Li was 2–3 times higher than the sputtering yield of D2 + on LiD. Incident 1000–1200 eV/D2 + sputtered LiO films at a slower rate than D2 + on LiD and LiCO films.